KAJIAN KONSEP TRI HITA KARANA PADA LEMBAGA SUBAK SEBAGAI SUMBERDAYA BUDAYA DI BALI (Studi Subak Juwuk Manis dan Subak Temesi di Kabupaten Gianyar) - USTRIYANA, I NYOMAN GEDE; ARTINI, NI WAYAN PUTU (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 9, No. 3 November 2009)
Bali has many traditional institutions which play important role in regional development. Subak, one of such is heritage of cultural sources
Keywords: Tri Hita Karana, subak cultural, resources